Conversational Topic Preferences, Taboo Words and Euphemisms Used by Male and Female Teachers of Pangasinan State University-Sta.Maria Campus - Perado, Marlon (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
Abstract Though teachers have the noblest profession, they are not exempted from using taboos and euphemisms. They also use a language they prefer to express themselves. This paper investigates the conversational topic preferences, use of taboo words, euphemisms, and cathartic words of teachers. Results of the study revealed that (1) sex is the most preferred topic by male teachers while work-related matters are for females; (2) in terms of topics that should be kept private, both groups dealt with personal lives; (3) both male and female teachers spill offensive words as cathartic expressions to show anger or fright; (4) when provoked, both respondents tend to utter harsh words to inflict insult or hurt on other people; (5) male utter more varied and more degrading expressions while females avoided the more insulting and derogatory cuss word; and (6) friends prove to be the most influential where they learn cuss words followed by media and neighborhood.